Effect of setting accelerator additive on short- and long-term properties of cold recycled mixture containing bitumen emulsion–cement composites. Issue 7 (2nd October 2020) - Abbasnejad, Seyed Yousof; Modarres, Amir
Abstract : Cold recycled layers have low early stiffness and are prone to rutting at initial days of curing. In this research, it was tried to resolve these issues by concurrent use of cement and chloride-free sodium carbonate-based accelerator. The cement content was fixed to 2% by weight of dry reclaimed asphalt pavement. The accelerator contents varied from 0% to 15% of the cement weight at 5% intervals. Experimental study was conducted on recycled mixes and emulsion–cement pastes. The partial and full curing protocols have been used to simulate the short- and long-term field curing processes, respectively. Marshall stability, indirect tensile strength and resilient modulus tests were accomplished on recycled mixes after both curing protocols and indirect tensile fatigue test was performed after the full curing process. Micro-structural analysis including the X-ray diffraction and scanning electron microscopy were conducted on cured pastes. Furthermore, the hydration heat release was measured by isothermal calorimetric procedure. It was concluded that the existence of emulsion in cement paste to some extent hindered the cement–water reactions. The addition of accelerator evidently increased the rate of cement hydration at initial days of curing and compensated the retarding effects of emulsion. For partially cured specimens, the strength and stiffness of recycled mixes containing accelerator was higher than the conventional mixture. However, a significant decrease in stiffness occurred after finishing the curing process for accelerator containing mixes. The retardation in portlandite development and growth of calcium carbonate crystals were the main reasons for stiffness decrease in these mixes after the full curing process.